IMPLEMENTASI KEBIJAKAN BUS RAPID TRANSIT (BRT) TRANS SEMARANG DI KOTA SEMARANG - Daniel Adam’s Siahaan; Ari Subowo; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Semarang city including the city experienced a fairly complicated transport problems, particularly road transport. Congestion in major cities, roads damaged, the terminal does not support, a growing number of vehicles, is not in line with the increase in capacity and access opening. As part of the effort to solve the congestion problem, the central government through the Ministry of Transportation propose the implementation of Bus Rapid Transit (BRT). The purpose of this study is to describe how the implementation of the BRT program in the city of Semarang and if it is in accordance with the applicable rules and to find out what are the constraints related to or are being faced in the implementation of BRT in the city of Semarang. This study used a qualitative approach with managers and HR Public Service Agency (BLU) Trans Semarang as the interviewer.The results in the development of BRT Trans Semarang constraints experienced by other anatar limited land BRT shelter placement on the right of way, the understanding of the shelter as utulitas by Highways that shelter placement should require permits, can not fulfill the contract mechanism plural, then the auction / tender providers services each year so that continuity of care is constrained at the beginning of the year, the limited ability of local budgets for fleet investment, travel speed bus yet eligible (still too soon exceed 8 km / h because of the standards set for congested areas or standard traffic mix is 10-12 km / h, the number of passengers has not been eligible for the hall I the average number of passengers per day by 5419 as much as standard from 1000 to 1200 and for corridor II of 2930 passengers per day with a standard 500-600 passengers per day.Suggestions presented in this study is the need for fleet expansion given the large number of passengers per day to meet the standards set by the Director General of Communication and Information, need to be reviewed on the performance of the crew bus driver, especially considering the speed of the vehicle exceeds the Directorate General of Land Transportation Standards. This is certainly endanger passengers and crew of the bus itself, need to increase coordination with relevant parties about the existence of shelters that shelter is expected to be in a strategic location, if necessary, plus amusing shleter to increase the capacity of passengers waiting for Bus Trans Semarang, facilities note the presence in the shelter as a place to sit or read media so that passengers feel comfortable.